Cation reduction and comproportionation as novel strategies to produce high voltage, halide free, carborane based electrolytes for rechargeable Mg batteries. Issue 12 (26th October 2015) - McArthur, Scott. G.; Geng, Linxiao; Guo, Juchen; Lavallo, Vincent
Abstract : The chemical reduction of reactive cations and comproportionation are two new strategies reported to produce halide free carborane based electrolytes for rechargeable Mg batteries. Abstract : Here we describe the cation reduction and comproportionation as novel routes to synthesize electrolytes for rechargeable Mg-ion batteries. Reduction of the ammonium cation in [HNMe3 1+ ][HCB11 H11 1− ] with metallic Mg affords the halide free carborane salt [Mg 2+ ][HCB11 H11 1− ]2 . Comproportionation of [Mg 2+ ][HCB11 H11 1− ]2 with MgPh2 affords the novel monocationic electrolyte [MgPh 1+ ][HCB11 H11 1− ], which reversibly deposits/strips Mg with a remarkable oxidative stability of 4.6 V vs. Mg 0/+2 .